Measuring concentrated poverty: Did it really decline in the 1990s - Todd Swanstrom; Rob Ryan; Katherine M. Stigers (University of California, Institute of Urban and Regional Development (IURD), 2007)
Scholars In the United States have almost universally defined concentrated poverty as census tracts in which a high percentage of the population (usually 40% plus) falls below the official federal poverty line. Few studies have asked the question that we ask here: what is the underlying concept behind concentrated poverty and, therefore, what is the best method for measuring it? The basic concept behind concentrated poverty is that people in such areas are unable to participate fully in the society around them. Based on a minimally acceptable diet, the federal poverty standard has become increasingly divorced from the realities of our affluent society and ignores differences in living standards across metropolitan areas. A definition of poverty based on 50 percent of median income in each region more accurately identifies people who are cut-off from mainstream society. Using such a relative poverty standard we show that concentrated poverty did not decline in the 1990s, as researchers using the federal standard concluded, but instead grew.
Keywords: 330; poverty; concentrated poverty; neighborhood effects